한국의 구조적 변화와 녹색성장 - 김용진 (12711, 2012)
Greenhouse gas emission policy in Korea and elsewhere is based on emissions projections, a key element of which is the projected path of structural change from high productivity growth to low productivity growth economic sectors given sector specific labo